Bacterial Profile and Antibiogram of Hospital-Acquired Pneumonia and Ventilator-Associated Pneumonia Patients in ICU of Raden Mattaher Hospital Jambi - Sotianingsih Sotianingsih; Samsirun H; Lipinwati Lipinwati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Pneumonia is defined as an inflammation of the lungs caused by microorganisms (bacteria, viruses, fungi, parasites). This research aimed to determine the pneumonia-causing bacteria along with the sensitivity and the antibiotic resistance test. This research was a descriptive study with samples of ICU pneumonia patients at Raden Mattaher Regional Hospital during the study period. All samples were consecutively selected. Samples for blood culture were incubated in the BactAlert device, whereas the sensitivity test was then performed using Vitex instruments. Sputum was previously enriched with BHI media and then cultured on culture media, and sensitivity test with the Vitex instruments was carried out. Of the 354 ICU patients during the study period, 30 patients (11.8%) had pneumonia, but only 19 patients could undergo sputum culture. Five of 19 patients were infected with Gram-positive bacteria, and 14 patients were infected with Gram-negative bacteria. The most commonly found bacteria were Klebsiella pneumonia (36.84%), followed by Acinetobacter baumanii (21.05%) and Pseudomonas aeruginosa (10.53%). Gram-negative bacteria obtained from sputum culture in this study were resistant to almost all antibiotic groups, especially penicillin, cephalosporin, quinolone, and tetracycline groups. Gram-positive bacteria obtained from sputum culture in this study were resistant to the penicillin antibiotic. The most commonly found bacteria were Klebsiella pneumonia (36.84%), followed by Acinetobacter baumanii (21.05%) and Pseudomonas aeruginosa (10.53%). The bacteria cultured from the sputum showed multidrug resistance mainly to the penicillin and cephalosporin antibiotic. This research data can be used to consider the treatment of pneumonia patients to decide more appropriate therapy.